Perceptions of Workplace Violence and Workplace Stress: A Mixed Methods Study of Trauma among Psychiatric Workers. (2nd September 2021) - Hilton, N. Zoe; Ricciardelli, Rosemary; Shewmake, James; Rodrigues, Nicole C.; Seto, Michael C.; Ham, Elke
Abstract: Posttraumatic stress disorder (PTSD) among psychiatric workers is related to workplace violence and work-specific stress. We used quantitative and qualitative approaches to survey PTSD symptoms, critical events, chronic exposures, and occupational stress in 84 psychiatric workers. All but three had directly experienced critical events, over half experienced someone's life being in danger, and 14% screened positive for PTSD. Symptoms correlated with critical events and perceived threat to life. Respondents described emergency codes, direct involvement, and repeated exposure as most stressful. Symptoms also correlated with nonviolent stressors, replicating previous research and indicating need to reduce both violence and workplace stress.